Menopausal hot flashing and endothelial function in two vascular beds: findings from a cross-sectional study of postmenopausal women. Issue 9 (September 2019) - Iliodromiti, Stamatina; Sattar, Naveed; Delles, Christian; Nelson, Scott M.; Gill, Jason M.R.; Lumsden, MaryAnn
Abstract: Objective: We sought to examine the association of menopausal hot flashing with vascular reactivity in two different vascular beds in the same cohort of postmenopausal women and explore the relationship between hot flashing and cardiovascular disease (CVD) risk profile. Methods: A cross-sectional study of 79 healthy postmenopausal women, 23 of whom have never had menopausal hot flashes and 56 of whom have reported hot flashes. Endothelial function at a microvascular level was measured with Laser Doppler Imaging with Iontophoresis which assesses the response to both acetylcholine (Ach, endothelium dependent) and sodium-nitroprusside (SNP, endothelium independent). Reactive Hyperemia Index (RHI) was measured with peripheral arterial tonometry as a marker of endothelial function mainly at a macrovascular level. Metabolic biomarkers including insulin sensitivity were assessed. Results: Women with hot flashes had enhanced microvascular response to Ach by ∼30% ( P = 0.04) and to SNP by ∼31% ( P = 0.02), but lower RHI by ∼13% ( P = 0.05) compared with women without flashes. Hot flashing was associated with enhanced response to SNP and lower RHI after adjustment for confounders and conventional CVD risk factors. Women with hot flashes were more insulin resistant than nonflashers (HOMAIR : 1.9 (1.2-2.6) vs 1.4 (0.8-1.9), P = 0.03). Conclusions: Our data support the association of hot flashing with greater insulin resistance and lower macrovascular response. The paradoxical enhanced microvascular response in hot flashers could be the result of the net effect of thermoregulatory and nonnitric oxide-related pathways rather than of endothelial integrity. Abstract : Supplemental Digital Content is available in the text